Implementasi Program Wirausaha Baru pada Dinas Tenaga Kerja dan Transmigrasi Provinsi Jambi - Anggi Natasya Santa Glorya (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The purpose of this study is to explore the implementation of the New Entrepreneur Program (WUB), to identify obstacles to the New Entrepreneur Program (WUB), to identify efforts made by the Jambi Province Manpower and Transmigration Office to overcome obstacles to the implementation of entrepreneurial policies. This study uses a Qualitative method with Data Collection Techniques carried out, namely Observation, Interviews and Documentation. The results of this study found that the Jambi Province New Entrepreneur Program (WUB) has succeeded in creating new entrepreneurs and reducing unemployment, but its effectiveness is hampered by less sustainable post-training assistance and a weak monitoring system. To improve implementation, it is necessary to strengthen the mentoring system and monitoring mechanism with accurate reporting applications. In addition, access to capital must be expanded through partnerships with financial institutions. Financial management training is also important, especially for elderly participants. It is hoped that the WUB program can be more effective in supporting entrepreneurial growth in Jambi Province.